The Effect Of Value Clarification Technique Learning Model On Critical Thinking Ability In PKn Subject In V Grade SDN 047 Inpres Baurung, Polewali Mandar - Nurfaizah A.P.; Nurfitriani Nurfitriani; Afdhal Fatawuri Syamsuddin (International Journal of Elementary School Teacher, 2023)
This research is an experimental research. This research is motivated by the lack of application of the VCT model in Civics learning which is able to attract students' attention resulting in low critical thinking skills. Research Objectives (1) To find out the application of Civics lessons using the VCT class V model at SDN 047 Inpres Baurung (2) To find out the critical thinking skills of class V students at SDN 047 Inpres Baurung (3) To find out the effect of the VCT learning model on critical thinking skills class V students at SDN 047 inpres baurung. The independent variable in this study is the use of the VCT learning model while the dependent variable is the ability to think critically. The research design was a Quasi Experimental Design using the Nonequivalent Control Group type. The data collection techniques used in this study were observation sheets of learning process activities, tests that were carried out twice, namely pretest and posttest tests and supporting learning tools for conducting research and research documentation. Research data analysis techniques using descriptive and inferential analysis. The results of the research that has been done can be concluded that: (1) the application of the VCT learning model to the critical thinking skills of Civics students of class V SDN 047 Inpres Baurung Kec. Campalagian District. Polewali Mandar. went well and effectively, this is evidenced by the results of observations of presentations in the very good category. (2) The ability to think critically shows an increase after giving the VCT learning model in learning activities. This is evidenced by the comparison of the average pretest scores for Civics learning outcomes in the experimental class as a whole and the posttest between the experimental class and the control class. (3) The use of the VCT learning model on students' Civics learning outcomes is said to have an effect, by proving based on the results of hypothesis testing, namely the probability value or the difference in test results obtained after learning using the VCT learning model.